Increased levels of chromosomal aberrations and DNA damage in a group of workers exposed to formaldehyde - Costa, S (2015)
Formaldehyde (FA) is a commonly used chemical in anatomy and pathology laboratories as a tissue preservative and fixative. Because of its sensitising properties, irritating effects and cancer implication, FA accounts probably for the most important chemical-exposure hazard concerning this professional group. Evidence for genotoxic effects and carcinogenic properties in humans is insufficient and conflicting, particularly in regard to the ability of inhaled FA to induce toxicity on other cells besides first contact tissues, such as buccal and nasal cells. To evaluate the effects of exposure to FA in human peripheral blood lymphocytes, a group of 84 anatomy pathology laboratory workers exposed occupationally to FA and 87 control subjects were tested for chromosomal aberrations (CAs) and DNA damage (comet assay). The level of exposure to FA in the workplace air was evaluated. The association between genotoxicity biomarkers and polymorphic genes of xenobiotic-metabolising and DNA repair enzymes were also assessed. The estimated mean level of FA exposure was 0.38±0.03 ppm. All cytogenetic endpoints assessed by CAs test and comet assay % tail DNA (%TDNA) were significantly higher in FA-exposed workers compared with controls. Regarding the effect of susceptibility biomarkers, results suggest that polymorphisms in CYP2E1 and GSTP1 metabolic genes, as well as, XRCC1 and PARP1 polymorphic genes involved in DNA repair pathways are associated with higher genetic damage in FA-exposed subjects. Data obtained in this study show a potential health risk situation of anatomy pathology laboratory workers exposed to FA (0.38 ppm). Implementation of security and hygiene measures may be crucial to decrease risk. The obtained information may also provide new important data to be used by health care programs and by governmental agencies responsible for occupational health and safety.